2019
DOI: 10.1007/s00432-019-02946-8
|View full text |Cite
|
Sign up to set email alerts
|

Human cytomegalovirus infection is correlated with enhanced cyclooxygenase-2 and 5-lipoxygenase protein expression in breast cancer

Abstract: Purpose While enhanced expression of cyclooxygenase-2 (COX-2) and 5-lipoxygenase (5-LO) and their derived metabolites is associated with breast cancer (BC) risk, the precise link between BC carcinogenesis and enhanced inflammatory activity remains to be clarified. Human Cytomegalovirus (HCMV) may induce expression of COX-2 and 5-LO and is frequently found in breast cancer biopsies. Thus, we investigated whether there is an association between HCMV proteins and expression of COX-2 and 5-LO in human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 67 publications
4
30
0
Order By: Relevance
“…In humans and mice, six, and in plants up to 23 LOX isoforms have been reported (Mashima and Okuyama, 2015;Upadhyay et al, 2019). While the overall structure of LOX enzymes seems to be similar, each isoform has unique properties such as substrate specificity and the expression level of each of them is differentially controlled (Costa et al, 2019;Mashima and Okuyama, 2015). In plants it has been shown that different stresses lead to differential expression of LOX family members and it is now accepted that LOX activity is a biological marker in plant stress tolerance (Babenko et al, 2017;Upadhyay et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In humans and mice, six, and in plants up to 23 LOX isoforms have been reported (Mashima and Okuyama, 2015;Upadhyay et al, 2019). While the overall structure of LOX enzymes seems to be similar, each isoform has unique properties such as substrate specificity and the expression level of each of them is differentially controlled (Costa et al, 2019;Mashima and Okuyama, 2015). In plants it has been shown that different stresses lead to differential expression of LOX family members and it is now accepted that LOX activity is a biological marker in plant stress tolerance (Babenko et al, 2017;Upadhyay et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The regulation of hypoxic signaling mechanisms further links this virus to cancer promotion [ 26 , 27 ]. CMV-induced inflammation, via the induced production of pro-inflammatory cytokines and expression of COX2 and 5-LO, can also enhance tumor aggressiveness [ 28 , 29 , 30 , 31 ], while simultaneously providing numerous immune evasion mechanisms to counteract the innate and adaptive immune responses to protect tumor cells from elimination by the immune system [ 32 ]. At least five CMV-encoded proteins and the long non-coding RNA β2.7 are anti-apoptotic and further promote cell survival [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Detection of HCMV-IE (using an antibody reacting with the immediate early nonstructural antigen of 68-72 kDa, Chemicon International), pp65 (BioGenex), and 5LO (Abcam) proteins in paraffin embedded tissue sections were performed by using an Immunohistochemistry (IHC) method as described previously. 7,8 For retrieval of epitopes on HCMV proteins for antibody binding, tissue sections were treated with pepsin (BioSite) for 3 min at 37°C and then in antigen retrieval Citra solution (Biosite), pH 7.6, in a 37°C water bath overnight. Antigen retrieval for targeting of 5LO epitopes was performed by treating the tissue sections in Citra Plus buffer pH 6.0 (BioGenex) in pressure cooker at 95°C for 20 min.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…Several studies have reported high prevalence of human cytomegalovirus (HCMV) proteins and nucleic acid in different types of cancer including ovarian, breast cancer, and glioblastoma multiforme with a potential negative impact on clinical outcome. [6][7][8] Furthermore, antiviral treatment of glioblastoma patients has indicated a prolonged overall survival. 9 This virus is reactivated by inflammation and promotes inflammation to secure its own existence, and a link has been proposed between HCMV, inflammation and cancer.…”
Section: Introductionmentioning
confidence: 99%